Effects of the inclusion of açai oil in diet of prepartum holstein cows on milk production, somatic cell counts and future lactation - Dos Santos D.S.* (2020)
© 2020, Academia Brasileira de Ciencias. All rights reserved.We measured the effects of açai oil in the diets of prepartum cows to evaluate health, milk production and quality. Sixteen Holstein cows were divided into two groups: SOY used as control, and AÇAI, test group. Occurred inclusion of 4% soybean or açai oils was provided in the concentrate starting at 20 days prepartum [d-20 to d 0 (partum-day)]. The AÇAI diet increased (P=0.01) milk production (d 10 and 20) and reduced somatic cell count (d 20). In milk, no effects were detected (P≥0.10) for concentration of fat, lactose or protein as well as in terms of serum concentration of calcium, albumin or triglycerides. AÇAI diet tended to increase (P=0.09) serum concentrations of total protein, glutathione transferase (d 4), and total antioxidant capacity (d 4 and 10) and increased (P≤0.05) globulin, gamma-glutamyl transferase, superoxide dismutase and glutathione peroxidase (d 4). Further, AÇAI diet reduced the serum concentration of creatine kinase (P≤0.05) (d 0, 4 and 10), reactive oxygen species (d 0 and 4) and lipoperoxidation (d 0) and tended to reduce aspartate transaminase activity (P=0.07; d 0 and 4). Açai oil in the diets in prepartum cows improved their health as well as milk production and quality.